Tests for jumps in yield spreads - Lars Winkelmann; Wenying Yao (Freie Universität Berlin, School of Business & Economics, 2021)
This paper develops high-frequency econometric methods to test for jumps in the spread of bond yields. We derive a coherent inference procedure that detects a jump in the yield spread only if at least one of the two underlying bonds displays a jump. We formalize the test as a sequential procedure in the context of an intersection union test in multiple testing and introduce a new bivariate jump test for pre-averaged intra-day returns. In an empirical application involving high-frequency data of U.S. government bonds, we contrast response patterns of term spreads and break-even in ation across monetary policy announcements, in ation, and employment news releases.
urn:nbn:de:kobv:188-refubium-32486-3
Keywords: C58; C12; E43; E44; 330; High-frequency data; sequential testing; news announcements; term spread; break-even inflation